FACTORS OF ACADEMIC DESERTION IN THE FACULTY OF PEDAGOGY OF THE TECHNICAL UNIVERSITY "LUIS VARGAS TORRES" OF ESMERALDAS - Toala Ponce , Santa; Galván Gracia, Nubia; Betancourt Sevilla, Gladys; Cambindo Quiñonez, Betsy; Vera Mera, Miryan (Revista Arbitrada Formación Gerencial, 2024)
Currently there are a large number of causes or factors of university desertion worldwide, so the objective of this article was to analyze in detail the factors of academic desertion in the Faculty of Pedagogy of the Technical University "Luis Vargas Torres" of Esmeraldas, in order to provide relevant information for the implementation of effective prevention and student retention measures. The study was developed with a descriptive, qualitative and quantitative design. The study population consisted of all students enrolled in the Faculty of Pedagogy of the "Luis Vargas Torres" Technical University of Esmeraldas during the academic period II semester 2022, a follow-up and study was carried out directed at 20 teachers and 180 students. Stratified random sampling was used to select a representative sample of students from different semesters and study programs. The technique used was the structured survey to collect data on the factors of academic dropout. And as a conclusion, it is important that the Technical University "Luis Vargas Torres" of Esmeraldas, as a higher education institution, is concerned with providing favorable institutional conditions for students from low socioeconomic levels, so that they can have a better academic performance.